Changes in beta 2-adrenoceptor and other signaling proteins produced by chronic administration of 'beta-blockers' in a murine asthma model (2007)
ABSTRACT: Background—We have previously reported that chronic treatment with certain ‘β-blockers’ reduces airway hyperresponsiveness (AHR) to methacholine in a murine model of asthma. Methods—Airway resistance was measured using the forced oscillation technique in ovalbulmin-sensitized and ovalbulmin-challenged mice treated with several β-adrenoceptor (β-AR) ligands. We used the selective β2-AR ligand ICI 118,551 and the preferential β1-AR ligand metoprolol to investigate the receptor subtype mediating the beneficial effect. Expression of β-ARs was evaluated using immunofluorescence. We evaluated several signaling proteins by western blot using lung homogenates, and measured the relaxation of the isolated trachea produced by EP2 and IP receptor agonists. Results—Four findings were associated with the decreased AHR after chronic β-blocker treatment: (1) the highly selective β2-AR antagonist/inverse agonist, ICI 118,551 produced the bronchoprotective effect; (2) β2-AR up-regulation resulted from chronic ‘β-blocker’ treatment; (3) reduced expression of certain proteins involved in regulating bronchial tone, namely, Gi, phosphodiesterase 4D and phospholipase C-β1; and (4) an enhanced bronchodilatory response to prostanoid agonists for the IP and EP2 receptors. Conclusions—These data suggest that in the murine model of asthma, several compensatory changes associated with either increased bronchodilator signaling or decreased bronchoconstrictive signaling, result from the chronic administration of certain ‘β-blockers’.